Investigation of 3-year inpatient TB cases in Zunyi, China: Increased TB burden but improved bacteriological diagnosis - Chen, Ling; Wang, Xiaodan; Jia, Xudong; Lan, Yuanbo; Yi, Haibo; Wang, Xiaomin; Xu, Peng (Frontiers in Public Health, 2022)
Background: As one of the top three high tuberculosis (TB) burden countries, China is a country where the overall TB incidence continues to decline. However, due to its large population and area, the increased TB burden exists in regional areas. Methods: This retrospective study analyzed local inpatient pulmonary TB cases in the Affiliated Hospital of Zunyi Medical University (AHZMU) from January 2016 to December 2018 in a high TB incidence and economically-less-developed area of China. Four methods, acid-fast bacilli stain, culture, Xpert and LAMP, were used to detect Mycobacterium tuberculosis (M.tb), while proportional method and Xpert were used to identify rifampicin-resistant TB (RR-TB). Case number, treatment history, M.tb confirmed TB and rifampicin resistant proportion were analyzed to investigate the local TB epidemic. Results: Total 3910 local inpatient cases with pulmonary TB were admitted to AHZMU during this study period. The annual numbers of total TB cases increased 26.4% (from 1173 to 1483), while new cases increased 29.6% (from 936 to 1213) and RR-TB cases increased 2.7 times (from 31 to 84). Meanwhile, the percentage of previously treated cases declined from 20.2% to 18.2% and the M.tb confirmed TB proportion increased from 34.7% to 49.7%. Conclusions: The elevated M.tb confirmed TB proportion and the declined percentage of previously treated cases indicated the improved TB diagnosis and treatment of AHZMU. However, the increasing number of total TB cases, new and RR-TB cases showed an upward trend and increased TB burden in a relatively underdeveloped area of China.